(untitled) (The Eurasia Proceedings of Science, Technology, Engineering and Mathematics, 2024)
The language of mass communication, on the one hand, enriches the literary language in its own way, saturating it with evaluative phrase, on the other hand, one cannot help but see the negative role of the language of some media technologies and gaming technologies of mass media, which is replete with various deviations from the norm, flooding speech with jargon and foreign words. The article reveals the concept of the “Global Network” - the Internet as a special media tool and how the Internet influences the development of language processes and education in the conditions of society digitalization. Definitions of words are given: language, media texts, linguistic culture, Internet, media, linguistic and cultural situation, Americanization, linguistic tradition and gaming technologies. Language is undergoing significant changes, and this article examines the role of media technologies in development and preservation of linguistic traditions. A huge role in human development and education belongs to the game. Game has an important impact in human’s life, what a person is in the game, so in many respects he will be in the work. It has been found that media game technologies have a significant influence in learning English language and culture. Gaming technologies improve speaking, listening, reading skills, develop logical thinking, form volitional, moral qualities of personality. Thus, the application of game elements in learning English helps to reveal students’ creative abilities, it is approved that in the game a student cognizes himself, his abilities and disadvantages. Nowadays, the state and position of media games technologies in learning English are been analyzed. This article describes and analyzes, the importance of the application of gaming technologies in the educational process, emphasizes the effectiveness of media game activities as the formation of personality, as an educational technology.